Influence of humic substances on iron distribution in the East China Sea. (August 2018) - Su, Han; Yang, Rujun; Li, Yan; Wang, Xuchen
Abstract: The influence of humic substances (specifically humic and fulvic acids, referred to as HS-HA and HS-FA) as well as other factors, such as major nutrient concentrations of total dissolved nitrogen (TDN), total dissolved phosphate (TDP) and hydrologic factors, on the distribution of total dissolved iron (DFe) and the chemical speciation of DFe was studied in the East China Sea (ECS) during a summer cruise in 2013. As the wide rage fraction of nature organic matter, the HS-HA, HS-FA in ESC contains most part of the organic ligand (Lt) of DFe. The concentrations of HS-HA, DFe and Lt in coastal water masses were higher than those in the water masses affected by the Kuroshio Current. The highest concentrations of HS-HA and DFe were observed in surface water at stations MT1 and MC4, with the value of 336.5 μg SRHA/L and 20.3 nmol/L, respectively, whereas, the lowest concentrations of HS-HA and DFe were observed in surface waters with the value of 149.6 μg SRHA/L and 0.4 nmol/L, respectively. HS-HA concentrations were more conservative than that of DFe. The DFe which were combined by unit weight HS-HA (mg −1, IB) in the surface and bottom waters quickly decreased with increasing salinities from the Yangtze River estuary to the southeast of the ECS. Average IB values in bottom waters were higher than those in surface waters. This study indicated that Yangtze River dilution water and cold water from the Yellow Sea were the main source of HS-HA and DFe in ECS. Highlights: YRDW and YSCW in the northeastern part of our research area are the main sources of DFe in the ECS in summer. In most samples, Lt is a part of HS-HA in the ECS, and HS-HA potentially complex the majority of DFe in seawater. IB ratio in the surfacewaters indicated a relatively higher Fe release than that of HS-HA in the bottom waters.